Pediatric chest X-ray diagnosis using neuromorphic models - Bokhari, Syed Mohsin; Sohaib, Sarmad; Shafi, Muhammad (Computers in biology and medicine, 2025)
This research presents an innovative neuromorphic method utilizing Spiking Neural Networks (SNNs) to analyze pediatric chest X-rays (PediCXR) to identify prevalent thoracic illnesses. We incorporate spiking-based machine learning models such as Spiking Convolutional Neural Networks (SCNN), Spiking Residual Networks (S-ResNet), and Hierarchical Spiking Neural Networks (HSNN), for pediatric chest radiographic analysis utilizing the publically available benchmark PediCXR dataset. These models employ spatiotemporal feature extraction, residual connections, and event-driven processing to improve diagnostic precision. The HSNN model surpasses benchmark approaches from the literature, with a classification accuracy of 96% across six thoracic illness categories, with an F1-score of 0.95 and a specificity of 1.0 in pneumonia detection. Our research demonstrates that neuromorphic computing is a feasible and biologically inspired approach to real-time medical imaging diagnostics, significantly improving performance. •This research underscores the effectiveness of SNN models in interpreting PCXR.•HSNN exhibited exceptional performance with a classification accuracy of 96%.•highlights the capacity of spiking neural networks for illness identification.